2010
DOI: 10.1002/jso.21580
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression profile of MAGE family in taiwanese patients with colorectal cancer

Abstract: This is the first comprehensive report to clarify the differential expression profile of whole MAGE family in CRCs, and it might provide some crucial information about the carcinogenesis and progression in Taiwanese patients with CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Melanoma-associated antigens (MAGE) are a group of well-characterized members of the cancer/testis antigen (CTA) family, which represents a unique class of tumor antigens that are expressed in a wide variety of malignant tumors 7 8 . MAGE-A is a subfamily comprising MAGE and MAGE-A antigens that are highly tumor specific; MAGE-A genes are anomalously expressed cancers though rarely expressed in normal tissues 9 .…”
mentioning
confidence: 99%
“…Melanoma-associated antigens (MAGE) are a group of well-characterized members of the cancer/testis antigen (CTA) family, which represents a unique class of tumor antigens that are expressed in a wide variety of malignant tumors 7 8 . MAGE-A is a subfamily comprising MAGE and MAGE-A antigens that are highly tumor specific; MAGE-A genes are anomalously expressed cancers though rarely expressed in normal tissues 9 .…”
mentioning
confidence: 99%
“…MAGED1 expression was also evaluated by Chung et al in Taiwanese CRC patients, and reported MAGED1 overexpression occurred in 45% CRC patients [15]. In the present study, 131 CRC patients were enrolled to compare their MAGED1 expression between colorectal cancer tissues and paired adjacent non-tumorous tissues.…”
Section: Discussionmentioning
confidence: 84%
“…Different from the MAGED1, MAGED12 was reported frequently up-regulated in tumors [15,17]. It was reported that MAGED1 and -D2 RNA had different distribution during the embryonic development and brain development [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure of the membrane array was performed based on our previously described protocol. 9 Subsequent quantification analysis of each spot's intensity was carried out using AlphaEase FC software (Alpha Innotech Corp., San Leandro, CA USA). The spots that consistently carried a factor of 2 were considered to be differentially expressed.…”
Section: Methodsmentioning
confidence: 99%